A convenient method for complex permittivity measurement of thin materials at microwave frequencies - Chung, B K (2006)
A practical problem in the reflection method for measuring permittivity of thin materials is the difficulty in ensuring the sample is placed exactly at the waveguide flange. A small position offset of the dielectric slab will give rise to significant errors in calculating the permittivity. To circumvent this problem, a measurement method using a waveguide partially filled with a thin material slab has been developed. The material sample can be easily prepared and inserted into the guide through a longitudinal slot on the broad wall of the waveguide. Multiple material slabs can be measured rapidly because one does not have to disconnect the waveguide system for sample placement. The method is verified with measurement of Teflon, glass and FR4 fibreglass. The measured permittivity show good agreement with published data. Subsequently, the permittivity of a vegetation leaf was measured. The method presented in this paper is particularly useful in measuring the permittivity of a thin and narrow slab of natural materials such as a paddy leaf.